Identifying an Institution to Become National Gas Aggregator Enity in Indonesia - Hutabarat, Ronald; Hamid Batubara, Abdul (The Indonesian Journal of Business Administration, 2017)
Abstract – The objective of this study is to formulate business model of an institution for national gas aggregator by using nine building blocks of the canvas business model.  This institution is expected to bridge the disparity of natural gas price between upstream producers and to provide standardization of natural gas price.  This step will be followed by calculating the gas price aggregators as a national reference for 2017.  This research is a case study that combines interviews, observations and analysis reports.  Data collection methods conducted by direct communications within SKK Migas as well as through observation and reporting on the relevant document, archives, and reports to learn and understand the current conditions regarding the utilization and patterns of natural gas sales in Indonesia as one but promising energy resources.  In order to address the natural gas price disparity from various region natural gas and to eliminate trader, it needs to set up an aggregation system that obliged each producers sale natural gas only through the institution and consumers only buy natural gas from the aggregator institution.  Nine building blocks of the canvas business model is structured to be able to run the aggregation system in order to eliminate the natural gas price disparity and natural gas sales execution which is conducted by the Government through national gas aggregator institution.  By using weighted average method plus alpha (where alpha is a component operational costs companies), the prices of natural gas price from the entity in 2017 is USD 5.36/MMBTU.  The price is still lower than the average gas price in the first quarter of 2017 of USD 5,55/MMBTU.Keywords: Natural Gas, Aggregator Price, Weighted Average Method, Nine Buildings Blocks of Business Model Canvas